Safety and efficacy of low-dose isotretinoin in the treatment of moderate to severe acne vulgaris - Parinitha K Rao; Ramesh M Bhat; B Nandakishore; Sukumar Dandakeri; Jacintha Martis; Ganesh H Kamath (Wolters Kluwer Medknow Publications, 2014)
Background: Isotretinoin is indicated for moderate to severe cases of acne which are unresponsive to conventional therapy. The classical recommended dose is 0.5 to 1.0 mg/kg/day. As the side effects are dose related, low-dose isotretinoin therapy for acne is an attractive option; however, but little data exists on the safety and efficacy of this strategy. Materials and Methods: In this prospective, non-comparative study, 50 participants, both male and female, having moderate to severe acne vulgaris were enrolled and treated with isotretinoin at a dose of 20 mg/day (approximately 0.3-0.4 mg/kg/day), for a period of 3 months. Participants were evaluated by means of clinical and laboratory investigations before starting isotretinoin. Investigations were repeated at the end of the first and third months following completion of treatment, and participants were followed up for 6 months to look for any relapse. Results: At the end of the treatment, very good results were observed in 90% of participants. Cheilitis was the most common among the side effects observed and was seen in 98% of the participants. One participant developed vitiligo as a side effect, which is a new finding, and has not reported in literature before. Elevated serum lipid levels were observed in 6% of the participants, and relapse occurred in 4% of the participants over a 6 month follow up period. Conclusion: Three months of treatment with low-dose isotretinoin (20 mg/day) was found to be effective in the treatment of moderate to severe acne vulgaris, with a low incidence of serious side effects. This dose also was more economical than the higher doses.